APLIKASI PENJUALAN BARANG LELANG PADA PT. PEGADAIAN (PERSERO) CPP. SIPIN AREA JAMBI BERBASIS ANDROID : ANDROID, APPLICATION, AUCTION GOODS, SALES, PEGADAIAN CPP. SIPIN. - Nurjani, Yeni (LP2M STMIK Nurdin Hamzah Jambi, 2018)
Current technological developments provide an important role in human life, especially in the business world because in a short time and a very wide distance, information can be delivered or received accurately and accurately. At this time PT. Pegadaian (Persero) CPP. Sipin still uses manual methods in the process of selling auction items and delivering information, including: banners, brochures, text messages and others. With the technology that is currently developing, especially the internet, a website is designed at PT. Pegadaian CPP. Civil servants are expected to be able to help PT. Pegadaian CPP. Sipin in facilitating the process of delivering information related to the scope of Sales of Auction Goods so that it can help the community in general. The information presented on this website includes the main page, starting from PT. Pegadaian CPP. Sipin, a brief history, vision and mission as well as facilities. Designing an Android-Based Information System at PT. Pegadaian CPP. This user uses java as a programming language and MySQL as its database.